Urgency Competence of Media Literacy for Archivist - Santoso, Agus (Record and Library Journal, 2016)
The study of media literacy has been conducted by the earlier scientists. That research uses population that have different characteristics to each other. So this studies of media literacy have various models or patterns. This models or patterns of media literacies will be used as basic data to the next study that generated will usually be the basis for the further research. Basically, the model of media literacy generated by some researchers only can be applied in the population which become objects of research. To day, the archives faced many challenges due to the presence of information technology, so that the competence of media literacy as one of the important competencies to have. through this competency, archivist are expected to manage archives organization effectively and efficiently. This paper uses a descriptive method to describe how media literacy becomes important for archives.